Evolution and trends in communication research about epidemics and pandemics at the international level - Ortiz Núñez, Roelvis (2021)
Communication research in times of epidemics and pandemics is an important factor in prevention, treatment and recovery. The study presented analyzes the behavior of communication research about epidemics and pandemics through the scientific production registered in the Scopus database. Indicators are used to assess general publication trends at the country, institutional, author, journal and article level. The prevailing themes and their evolution over time are examined, as well as the evolution in the groups and associated research fronts. The results show a trend towards the growth of publications with a higher concentration in 2020. The number of publications by countries, institutions, authors and journals is discrete, therefore, it is an area of ​​knowledge that requires greater scientific research and international collaboration. Five major thematic groups, main emerging research focuses, related to health communication during epidemics, social attitudes towards health, communication during influenza A H1N1 and the COVID-19 pandemic, and epidemiological information on social networks were identified. The critical points of research in the field during the 30 years recorded in the Scopus database allow us to infer that communication about epidemics and pandemics should become the focus of research in the area of ​​risk communication in the near future